Diálisis peritoneal - Herrera Chambilla, Caleb Alexander (2021)
Peritoneal dialysis (PD) is a treatment used in patients with kidney failure, it consists of the purification of harmful substances from the harmless ones and not only that, but it also allows the elimination of excess electrolytes in the body, thanks to the fact that it uses the coating of the abdomen called "peritoneal membrane" as a filter. A review article was made of 21 bibliographic works, from which the essential information was extracted. A history of peritoneal dialysis is shown, implements such as the catheter and dialysate solution, types of PD treatment: Continuous Ambulatory Peritoneal Dialysis (CAPD) and Automated Peritoneal Dialysis (APD): adapted Automated Peritoneal Dialysis (aAPD), Tidal Peritoneal Dialysis (TPD), Continuous Cyclic Peritoneal Dialysis (CCPD), Nocturnal Intermittent Peritoneal Dialysis (NIPD) and Intermittent Peritoneal Dialysis (IPD). Finally, the most common complications that can occur from PD treatment are mentioned, such as peritonitis or infection of the exit site and subcutaneous tunnel.